High-strength corrosion-resistant ABS composite flame-retardant material and preparation method thereof
By leveraging the synergistic effect of epoxy-modified graphene oxide and modified nano-montmorillonite with glass fiber, the problems of insufficient strength, corrosion resistance and flame retardancy in ABS materials have been solved, achieving comprehensive performance of high strength, corrosion resistance and high flame retardancy.
Patent Information
- Application Number
- CN202411816212.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-01-10
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing ABS materials have shortcomings in terms of strength, corrosion resistance and flame retardancy. They are difficult to maintain stable performance in high-temperature or corrosive environments. The compatibility of traditional reinforcing fillers and flame retardants is limited, which makes the materials brittle under impact and poses safety hazards.
Epoxy-modified graphene oxide and long-chain alkylsilane-modified nano-montmorillonite are synergistically reinforced with glass fiber. The mechanical properties and flame retardant effect of the ABS matrix are improved through interfacial bonding and dispersibility, forming a multi-layer flame retardant barrier. Combined with phosphorus and nitrogen flame retardants and nano-alumina, the flame retardancy is further enhanced.
It significantly improves the mechanical strength, corrosion resistance and flame retardancy of ABS composite materials, extends the service life of materials in harsh environments, reduces the release of toxic gases and smoke emissions, and achieves comprehensive performance of high strength, corrosion resistance and high flame retardancy.
Smart Images

Figure CN119286187A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer composite materials, and particularly relates to a high-strength corrosion-resistant ABS composite flame-retardant material and a preparation method thereof. Background Art
[0002] ABS (Acrylonitrile-Butadiene-Styrene) materials are widely used in the fields of automobiles, electronics, electrical appliances and construction due to their good toughness, impact resistance and processing properties. However, with the increasing demand for material performance, there are increasing requirements for the modification of ABS materials in terms of strength, corrosion resistance and flame retardancy to meet the application in special environments. As an amorphous thermoplastic polymer, ABS material has excellent mechanical properties, toughness and formability, but its own corrosion resistance and flame retardancy are weak. It is easy to decompose or burn in high temperature or corrosive environment, which limits its promotion in applications requiring high weather resistance and flame retardancy. In order to improve the strength of ABS, glass fiber, carbon fiber, nano-carbon tubes or inorganic fillers (such as SiO2, Al2O3) are often used as reinforcing fillers. These materials can not only improve the strength and rigidity of ABS composite materials, but also improve their wear resistance and creep resistance. In particular, the introduction of nanomaterials can strengthen the interaction between molecular chains at the microscopic level and improve the overall strength and stability of the material. ABS material itself is a flammable material, so there are safety hazards under high temperature or open flame conditions. The use of flame retardants (such as bromine-based, phosphorus-based, nitrogen-based flame retardants or halogen-free flame retardants) can effectively reduce the burning rate of materials. In particular, the flame retardant system of phosphorus and nitrogen synergy can enhance the flame retardant effect and reduce the heat release. However, although ordinary fillers (such as glass fiber and carbon fiber) can enhance strength, they may also cause the toughness of ABS materials to decrease, and the materials are easy to break under impact and lack flexibility. In addition, the compatibility of traditional flame retardants and reinforcing fillers is limited, and it is difficult to achieve a balance between mechanical properties and flame retardant properties. Commonly used bromine-based flame retardants have environmental problems and release toxic gases. Although halogen-free flame retardants are safer, their flame retardant effect is weaker. In addition, after adding flame retardants, the material is prone to yellowing, strength reduction and other problems, which affect the long-term performance of the material. Therefore, based on the above problems, it is extremely necessary to develop a high-strength and corrosion-resistant ABS composite flame retardant material. Summary of the invention
[0003] In view of the defects of the prior art, the object of the present invention is to provide a high-strength, corrosion-resistant ABS composite flame-retardant material and a preparation method thereof.
[0004] The technical effect described in the present invention is achieved through the following technical scheme: a high-strength, corrosion-resistant ABS composite flame-retardant material, which comprises the following raw materials in parts by weight: 60 to 75 parts of acrylonitrile-butadiene-styrene, 10 to 15 parts of glass fiber, 0.5 to 1 part of γ-aminopropyltriethoxysilane, 8 to 12 parts of phosphorus-nitrogen flame retardant, 1 to 3 parts of nano-alumina, 0.5 to 1 part of potassium perfluorooctane sulfonate, 1 to 3 parts of epoxy-modified graphene oxide, and 5 to 8 parts of modified nano-montmorillonite.
[0005] Preferably, the phosphorus-nitrogen flame retardant is any one of tricresyl phosphate, trimethyl phosphate, triethyl phosphate and ammonium polyphosphate.
[0006] Preferably, the specific preparation steps of the epoxy-modified graphene oxide are as follows: Ⅰ: Add graphene oxide to anhydrous ethanol, and perform ultrasonic treatment at a power of 200 to 300 W, a frequency of 40 kHz, and a time of 30 to 50 min to obtain a graphene oxide dispersion; slowly add 3-glycidyloxypropyltrimethoxysilane to the graphene oxide dispersion, increase the temperature to 60 to 70° C., and stir at a speed of 300 rpm for 2 to 3 hours; Ⅱ: After the solution reaction in step Ⅰ is completed, the solution is cooled to room temperature, washed with deionized water, centrifuged at 5000 rpm for 10 min, washed three times, and vacuum dried at 60° C. to constant weight to obtain epoxy-modified graphene oxide.
[0007] Preferably, in step I, the ratio of the amount of graphene oxide to deionized water is 0.1-0.2 g:50 mL; the ratio of the amount of graphene oxide to 3-glycidyloxypropyltrimethoxysilane is 0.5 g:0.8-1 mL.
[0008] Preferably, the specific preparation steps of the modified nano-montmorillonite are as follows: (1): Add nano-montmorillonite to anhydrous ethanol, with a power of 100-150 W and a frequency of 30 kHz, and perform ultrasonic treatment for 15-30 min to obtain a nano-montmorillonite suspension; slowly add octadecyltrichlorosilane to the nano-montmorillonite suspension within 10 min, increase the temperature to 50-60° C., control the pH to be neutral, and stir at 300 rpm for 3-5 h; (2): After the reaction in step (1) is completed, the mixture is allowed to stand and cool to room temperature, and deionized water and ethanol are added for washing alternately. The mixture is centrifuged at 3000 rpm for 10 min, and the washing is repeated 3 to 5 times. The mixture is vacuum dried at 60° C. to a constant weight to obtain modified nano-montmorillonite.
[0009] Preferably, in step (1), the ratio of the amount of the nano-montmorillonite to anhydrous ethanol is 1 g: 20-25 mL; the ratio of the amount of octadecyltrichlorosilane to the nano-montmorillonite is 2-2.5 mL: 1 g.
[0010] Preferably, another aspect of the present invention is to provide a method for preparing a high-strength, corrosion-resistant ABS composite flame-retardant material, and the specific preparation steps are as follows: S1: adding γ-aminopropyltriethoxysilane to anhydrous ethanol, stirring and mixing to obtain a 1wt% coupling agent solution; immersing the glass fiber in the coupling agent solution, standing for 30 to 60 minutes, and drying at 80 to 100°C to constant weight to obtain a pretreated glass fiber; S2: adding epoxy-modified graphene oxide, modified nano-montmorillonite, phosphorus-nitrogen flame retardant, nano-alumina and potassium perfluorooctane sulfonate into a mixer in sequence, stirring and mixing at 500-1000 rpm for 5-10 minutes to obtain a premix; S3: Add acrylonitrile-butadiene-styrene into an extruder, preheat to 200-220°C for preliminary melting, then gradually add the premix prepared in step S2 and the pretreated glass fiber prepared in step S1, set the extrusion speed to 60-120rpm, the melting temperature to 200-240°C, the extrusion speed to 1-3m / min, and quickly cool the extruded material through a cooling water tank to obtain an ABS composite flame retardant material.
[0011] The beneficial effects of the present invention are as follows: The present invention significantly enhances the mechanical properties, corrosion resistance and flame retardant effect of an acrylonitrile-butadiene-styrene (ABS) matrix through the synergistic effect of epoxysilane-modified graphene oxide (GO) and long-chain alkylsilane-modified nano-montmorillonite. The modified graphene oxide surface carries epoxy groups, which significantly improve the dispersibility and compatibility of graphene oxide in the ABS matrix by enhancing the interfacial bonding force, and constructs a uniform enhanced network structure; at the same time, the silane group gives the graphene oxide sheet a certain flexibility, so that the material maintains toughness under high-strength conditions and effectively avoids embrittlement. The nano-montmorillonite modified by the long-chain alkylsilane significantly reduces the surface polarity, improves the lipophilicity and enhances its dispersion uniformity in the ABS matrix through the hydrophobicity and low polarity of the long-chain hydrocarbon group, effectively avoids agglomeration, constructs a more stable composite structure, enhances the rigid support effect of the overall material, and enables the composite material to have both high strength and toughness. In terms of interface, the interfacial bonding force between modified graphene oxide and glass fiber is formed through the reaction of silane groups with the hydroxyl groups on the surface of glass fiber to form a strong silicon-oxygen bond, which significantly improves the chemical bonding strength between the interfaces; at the same time, the modified graphene oxide is evenly dispersed around the glass fiber, filling the irregular micropores and microcracks on the fiber surface during the curing process, forming a "mechanical locking" effect, further enhancing the interfacial bonding force; the modified nano-montmorillonite is evenly distributed in the matrix, forming a triple composite structure with graphene oxide and glass fiber. The epoxy-modified graphene oxide is tightly bonded to the ABS matrix through chemical bonds, the modified nano-montmorillonite provides rigid support through interlayer cross-linking, and the glass fiber optimizes the mechanical properties through mechanical locking and stress dispersion. The synergistic effect of the three not only significantly improves the mechanical strength and impact resistance of the composite material, but also improves its thermal stability and long-term corrosion resistance, ensuring that the material exhibits excellent performance in various application environments.
[0012] The present invention utilizes the compact layered structure and good hydrophobicity of modified graphene oxide to effectively block the penetration of moisture, corrosive ions and chemical substances, and prolong the service life of the material in acidic, alkaline and high-salt environments. The modified nano-montmorillonite is stably dispersed in the ABS matrix, avoiding the risk of agglomeration or stratification caused by environmental changes, and ensuring the long-term corrosion resistance of the material; the modified nano-montmorillonite enhances the barrier properties of the material through its hydrophobicity and interlayer cross-linked structure, and improves the stability in harsh environments; the increase in the interlayer spacing of montmorillonite is conducive to peeling and dispersion in the ABS matrix, forming a nano-scale network structure, enhancing the barrier properties and mechanical properties, and forming multi-point connections with glass fibers and graphene oxide through organic functional groups, thereby improving the structural stability.
[0013] The present invention utilizes the dense carbon layer formed by graphene oxide at high temperature to block the conduction of oxygen and heat source, and combines with the lamellar structure of nano-montmorillonite to form a multi-level flame retardant barrier, which significantly delays the spread of flame. Graphene oxide blocks the conduction of oxygen and heat source through the formation of a carbonized layer during the combustion process, and synergizes with the lamellar structure of nano-montmorillonite to delay the spread of flame. In addition, the barrier property of graphene oxide reduces the internal heat accumulation of the material, thereby indirectly achieving a cooling effect, and introduces phosphorus-nitrogen flame retardants and a small amount of nano-alumina to further improve the flame retardant effect. The phosphorus-nitrogen flame retardant reduces the generation of combustible gas by promoting carbonization, and nano-alumina delays the combustion process through its excellent thermal insulation performance and the protective effect of the carbonized layer. The synergistic effect of the two significantly reduces the release of toxic gases, so that the material has a longer fire resistance limit and lower smoke emissions in a high temperature environment, and the environmental protection is significantly improved. In terms of microstructure, modified montmorillonite and modified graphene oxide form a microscopic network with ABS matrix and glass fiber at the nanoscale, and construct a nano-level reinforcement network through interlayer crosslinking and chemical bonding; glass fiber, as a macroscopic reinforcement phase, forms a continuous fiber network, and together with nanofillers, constructs a multi-scale three-dimensional network structure; modified nano-montmorillonite and graphene oxide act as nano-barrier layers to hinder crack propagation and improve impact resistance and toughness. Glass fiber forms a physical barrier in the direction of crack propagation, further preventing crack propagation and brittle failure. Nanofillers form a physical interlocking structure on the surface of glass fiber, improving interface stability and mechanical locking, and achieving effective dispersion and transmission of stress. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only for the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0015] Figure 1 It is a graph showing the corrosion resistance test results of the ABS composite flame retardant materials prepared in Example 2 of the present invention and Comparative Examples 1 to 4; Figure 2 It is a graph showing the oxygen index results of the flame retardancy test of the ABS composite flame retardant materials prepared in Example 2 of the present invention and Comparative Examples 1 to 4; Figure 3 It is a graph showing the decomposition temperature results of the thermal stability test of the ABS composite flame retardant materials prepared in Example 2 of the present invention and Comparative Examples 1 to 4. DETAILED DESCRIPTION
[0016] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. It should be noted that, unless otherwise specified, the raw materials involved in the present invention are purchased through conventional commercial channels.
[0017] Embodiment 1: A high-strength, corrosion-resistant ABS composite flame-retardant material, which comprises the following raw materials in parts by weight: 60 parts of acrylonitrile-butadiene-styrene, 10 parts of glass fiber, 0.5 parts of γ-aminopropyltriethoxysilane, 8 parts of phosphorus nitrogen flame retardant, 1 part of nano-alumina, 0.5 parts of potassium perfluorooctane sulfonate, 1 part of epoxy-modified graphene oxide, and 5 parts of modified nano-montmorillonite.
[0018] The specific preparation steps of epoxy-modified graphene oxide are as follows: Ⅰ: Add 1 g of graphene oxide to 500 mL of anhydrous ethanol, and ultrasonically treat at a power of 200 W, a frequency of 40 kHz, and a time of 50 min to obtain a graphene oxide dispersion; slowly add 1.6 mL of 3-glycidyloxypropyltrimethoxysilane to the graphene oxide dispersion, increase the temperature to 60°C, and stir at 300 rpm for 2 h; Ⅱ: After the solution reaction in step Ⅰ is completed, the solution is cooled to room temperature, washed with deionized water, centrifuged at 5000 rpm for 10 min, washed three times, and vacuum dried at 60°C to constant weight to obtain epoxy-modified graphene oxide; The specific preparation steps of modified nano-montmorillonite are as follows: (1): 10 g of nano-montmorillonite was added to 200 mL of anhydrous ethanol, and the power was 100 W, the frequency was 30 kHz, and the ultrasonic treatment was performed for 30 min to obtain a nano-montmorillonite suspension; 20 mL of octadecyltrichlorosilane was slowly added to the nano-montmorillonite suspension within 10 min, the temperature was increased to 50 ° C, the pH was controlled to be neutral, and the reaction was stirred at 300 rpm for 3 h; (2): After the reaction in step (1) is completed, the mixture is allowed to stand and cool to room temperature, and deionized water and ethanol are added for washing alternately, centrifuged at 3000 rpm for 10 min, and the washing is repeated three times. The mixture is vacuum dried at 60° C. to a constant weight to obtain modified nano-montmorillonite; The specific preparation steps of high-strength corrosion-resistant ABS composite flame retardant material are as follows: S1: Add γ-aminopropyltriethoxysilane to anhydrous ethanol, stir and mix evenly to obtain a 1wt% coupling agent solution; immerse the glass fiber in the coupling agent solution, let it stand for 30 minutes, and dry it at 80°C to constant weight to obtain a pretreated glass fiber; S2: adding epoxy-modified graphene oxide, modified nano-montmorillonite, phosphorus-nitrogen flame retardant, nano-alumina and potassium perfluorooctane sulfonate into a mixer in sequence, stirring and mixing at 500 rpm for 10 min to obtain a premix; S3: Add acrylonitrile-butadiene-styrene into the extruder, preheat to 200°C for preliminary melting, then gradually add the premix prepared in step S2 and the pretreated glass fiber prepared in step S1, set the extrusion speed to 60 rpm, the melting temperature to 200°C, the extrusion speed to 1 m / min, and quickly cool the extruded material through a cooling water tank to obtain an ABS composite flame retardant material.
[0019] Example 2: A high-strength, corrosion-resistant ABS composite flame-retardant material, which is composed of the following raw materials in parts by weight: 70 parts of acrylonitrile-butadiene-styrene, 15 parts of glass fiber, 1 part of γ-aminopropyltriethoxysilane, 12 parts of phosphorus-nitrogen flame retardant, 3 parts of nano-alumina, 1 part of potassium perfluorooctane sulfonate, 3 parts of epoxy-modified graphene oxide, and 8 parts of modified nano-montmorillonite.
[0020] The specific preparation steps of epoxy-modified graphene oxide are as follows: Ⅰ: 1.8 g of graphene oxide was added to anhydrous ethanol, and ultrasonic treatment was performed at a power of 250 W, a frequency of 40 kHz, and a time of 40 min to obtain a graphene oxide dispersion; 3.5 mL of 3-glycidyloxypropyltrimethoxysilane was slowly added to the graphene oxide dispersion, the temperature was increased to 70°C, and the reaction was stirred at a speed of 300 rpm for 2.5 h; Ⅱ: After the solution reaction in step Ⅰ is completed, the solution is cooled to room temperature, washed with deionized water, centrifuged at 5000 rpm for 10 min, washed three times, and vacuum dried at 60°C to constant weight to obtain epoxy-modified graphene oxide; The specific preparation steps of modified nano-montmorillonite are as follows: (1): 10 g of nano-montmorillonite was added to 240 mL of anhydrous ethanol, and the power was 120 W, the frequency was 30 kHz, and the ultrasonic treatment was performed for 25 min to obtain a nano-montmorillonite suspension; 24 mL of octadecyltrichlorosilane was slowly added to the nano-montmorillonite suspension within 10 min, the temperature was increased to 55 ° C, the pH was controlled to be neutral, and the reaction was stirred at 300 rpm for 4 h; (2): After the reaction in step (1) is completed, the mixture is allowed to stand and cool to room temperature, and deionized water and ethanol are added for washing alternately, centrifuged at 3000 rpm for 10 min, and the washing is repeated 5 times. The mixture is vacuum dried at 60° C. to a constant weight to obtain a modified nano-montmorillonite; The specific preparation steps of high-strength corrosion-resistant ABS composite flame retardant material are as follows: S1: Add γ-aminopropyltriethoxysilane to anhydrous ethanol, stir and mix evenly to obtain a 1wt% coupling agent solution; immerse the glass fiber in the coupling agent solution, let it stand for 50 minutes, and dry it at 90°C to constant weight to obtain a pretreated glass fiber; S2: adding epoxy-modified graphene oxide, modified nano-montmorillonite, phosphorus-nitrogen flame retardant, nano-alumina and potassium perfluorooctane sulfonate into a mixer in sequence, stirring and mixing at 800 rpm for 8 minutes to obtain a premix; S3: Add acrylonitrile-butadiene-styrene into the extruder, preheat to 210°C for preliminary melting, then gradually add the premix prepared in step S2 and the pretreated glass fiber prepared in step S1, set the extrusion speed to 80 rpm, the melting temperature to 220°C, the extrusion speed to 2 m / min, and quickly cool the extruded material through a cooling water tank to obtain an ABS composite flame retardant material.
[0021] Example 3: A high-strength, corrosion-resistant ABS composite flame-retardant material, which is composed of the following raw materials in parts by weight: 75 parts of acrylonitrile-butadiene-styrene, 14 parts of glass fiber, 0.8 parts of γ-aminopropyltriethoxysilane, 10 parts of phosphorus-nitrogen flame retardant, 2 parts of nano-alumina, 0.8 parts of potassium perfluorooctane sulfonate, 2 parts of epoxy-modified graphene oxide, and 7 parts of modified nano-montmorillonite.
[0022] The specific preparation steps of epoxy-modified graphene oxide are as follows: Ⅰ: Add 2 g of graphene oxide to 500 mL of anhydrous ethanol, and ultrasonically treat at a power of 300 W, a frequency of 40 kHz, and a time of 30 min to obtain a graphene oxide dispersion; slowly add 4 mL of 3-glycidyloxypropyltrimethoxysilane to the graphene oxide dispersion, increase the temperature to 70°C, and stir at 300 rpm for 2 h; Ⅱ: After the solution reaction in step Ⅰ is completed, the solution is cooled to room temperature, washed with deionized water, centrifuged at 5000 rpm for 10 min, washed three times, and vacuum dried at 60°C to constant weight to obtain epoxy-modified graphene oxide; The specific preparation steps of modified nano-montmorillonite are as follows: (1): 10 g of nano-montmorillonite was added to 250 mL of anhydrous ethanol, and the power was 150 W, the frequency was 30 kHz, and the ultrasonic treatment was performed for 15 min to obtain a nano-montmorillonite suspension; 25 mL of octadecyltrichlorosilane was slowly added to the nano-montmorillonite suspension within 10 min, the temperature was increased to 60 ° C, the pH was controlled to be neutral, and the reaction was stirred at 300 rpm for 3 h; (2): After the reaction in step (1) is completed, the mixture is allowed to stand and cool to room temperature, and deionized water and ethanol are added for washing alternately, centrifuged at 3000 rpm for 10 min, and the washing is repeated 4 times. The mixture is vacuum dried at 60° C. to a constant weight to obtain modified nano-montmorillonite; The specific preparation steps of high-strength corrosion-resistant ABS composite flame retardant material are as follows: S1: Add γ-aminopropyltriethoxysilane to anhydrous ethanol, stir and mix evenly to obtain a 1wt% coupling agent solution; immerse the glass fiber in the coupling agent solution, let it stand for 60 minutes, and dry it at 100°C to constant weight to obtain a pretreated glass fiber; S2: adding epoxy-modified graphene oxide, modified nano-montmorillonite, phosphorus-nitrogen flame retardant, nano-alumina and potassium perfluorooctane sulfonate into a mixer in sequence, stirring and mixing at 1000 rpm for 5 minutes to obtain a premix; S3: Add acrylonitrile-butadiene-styrene into the extruder, preheat to 220°C for preliminary melting, then gradually add the premix prepared in step S2 and the pretreated glass fiber prepared in step S1, set the extrusion speed to 120 rpm, the melting temperature to 240°C, the extrusion speed to 3 m / min, and quickly cool the extruded material through a cooling water tank to obtain an ABS composite flame retardant material.
[0023] Comparative Example 1: The operation of Comparative Example 1 is substantially the same as that of Example 2, except that epoxy-modified graphene oxide is not added in Comparative Example 1.
[0024] Comparative Example 2: The operation of Comparative Example 2 is substantially the same as that of Example 2, except that graphene oxide is used in Comparative Example 2 to replace epoxy-modified graphene oxide.
[0025] Comparative Example 3: The operation of Comparative Example 3 is basically the same as that of Example 2, except that in Comparative Example 3, nano-montmorillonite is used to replace modified nano-montmorillonite.
[0026] Comparative Example 4: The operation of Comparative Example 4 is substantially the same as that of Example 2, except that no glass fiber is added in Comparative Example 4.
[0027] Performance Testing: Mechanical property test: The tensile strength, flexural strength and impact strength of the ABS composite flame retardant material samples prepared in Examples 1 to 3 and Comparative Examples 1 to 4 were tested using a universal material testing machine. The results are shown in Table 1 below.
[0028] Table 1. Mechanical strength test results of ABS composite flame retardant materials
[0029] It can be seen from the results in Table 1 that the ABS composite flame retardant material prepared by the present invention exhibits excellent mechanical properties based on the synergistic effect between various substances; it can be seen from the results of Comparative Example 1 and Example 2 that the epoxy-modified graphene oxide is tightly bonded to the ABS matrix interface through the epoxy group, which can significantly enhance the interfacial bonding force. The lack of this material leads to insufficient interfacial bonding force and poor stress dispersion effect. In addition, due to the lack of a flexible reinforcement layer, this may cause the material to be more susceptible to stress concentration during stretching and impact, thereby resulting in significant differences in its mechanical properties; it can be seen from the results of Comparative Example 2 and Example 2 that the surface of ordinary graphene oxide lacks epoxy groups, which may lead to weak interfacial bonding force with the ABS matrix, and the flexibility of ordinary graphene oxide is poor. The effect is not as good as that of epoxy modified materials, which leads to a certain degree of influence on the mechanical properties of the material; from the results of Comparative Example 3 and Example 2, it can be seen that the surface polarity of the unmodified nano-montmorillonite is strong, it is easy to agglomerate in the ABS matrix, the dispersion is uneven, the composite reinforcement effect is weakened, and the rigid support effect is significantly reduced, and the unmodified nano-montmorillonite is difficult to effectively participate in the interface effect of the matrix, which to a certain extent reduces the overall mechanical properties of the material; from the results of Comparative Example 4 and Example 2, it can be seen that the glass fiber plays a role in uniformly dispersing stress in the reinforcement network, and effectively achieves synergistic effect with graphene oxide and nano-montmorillonite. The material lacking glass fiber has a significantly reduced synergistic effect, which is easy to cause stress concentration, thereby leading to a decrease in overall mechanical properties.
[0030] Corrosion resistance test: Use 5% NaCl solution to continuously spray the ABS composite flame retardant material samples prepared in Example 2 and Comparative Examples 1 to 4 at 35°C for 16 hours, then stop for 8 hours, and test for a total of 96 hours. The surface changes of the ABS composite flame retardant material are recorded at 24 hours, 48 hours and 96 hours, respectively. The results are shown in Table 2 below; The ABS composite flame retardant material samples prepared in Example 2 and Comparative Examples 1 to 4 were immersed in HCl solution (pH=2) and NaOH solution (pH=12) for 168 hours, and the tensile strength change percentage (%) was recorded = (tensile strength before immersion-tensile strength after immersion) / tensile strength before immersion × 100%. The results are shown in Table 2 below. Figure 1 shown.
[0031] Table 2. Corrosion resistance test results of ABS composite flame retardant materials
[0032] From Table 2 and Figure 1The results show that the ABS composite flame retardant material prepared by the present invention has excellent corrosion resistance; the results of comparative example 1 and embodiment 2 show that due to the lack of epoxy-modified graphene oxide, this may lead to the inability to form a dense interface bonding network, insufficient barrier performance, and at the same time, due to insufficient interface bonding force and dispersibility, micropores or defects may be formed inside the composite material, and the penetration of corrosive media through these paths is accelerated, resulting in a significant decrease in corrosion resistance; the results of comparative example 2 and embodiment 2 show that the dispersibility of ordinary graphene oxide is not as good as that of epoxy-modified materials, and it is easy to agglomerate, which may This results in weak corrosion resistance in local areas and the appearance of local corrosion spots; from the results of Comparative Example 3 and Example 2, it can be seen that the agglomeration phenomenon of nano-montmorillonite in the matrix is obvious, resulting in uneven distribution of the barrier layer, thereby forming a corrosion channel, and the high surface polarity of the unmodified nano-montmorillonite leads to a decrease in the hydrophobicity of the material, which is easy to absorb moisture and accelerate the penetration of corrosive media, resulting in a significant decrease in corrosion resistance; from the results of Comparative Example 4 and Example 2, it can be seen that the rigid supporting role of the glass fiber is lost, the structural stability of the material is reduced, the mechanical properties are significantly reduced, and the corrosion resistance is affected to a certain extent.
[0033] Flame retardancy test: The ABS composite flame retardant material samples prepared in Example 2 and Comparative Examples 1 to 4 were fixed vertically, and the standard flame ignited the bottom of the test (10s). The flame extinguishing time and whether the dripping material was burning were recorded. The results are shown in Table 3 below. The ABS composite flame retardant material samples prepared in Example 2 and Comparative Examples 1 to 4 were placed in a mixed gas environment, and the proportion of oxygen was gradually increased until the sample could just continue to burn. The minimum oxygen percentage required for the sample to continue to burn was recorded. The results are shown in Table 3 below. Figure 2 shown.
[0034] Table 3. Flame retardancy test results of ABS composite flame retardant materials
[0035] From Table 3 and Figure 2As can be seen from the results, the ABS composite flame retardant material prepared by the present invention has an excellent flame retardant effect, an extremely high oxygen index, and the burning dripping material no longer continues to burn and is extinguished very quickly; from the results of Comparative Example 1 and Example 2, it can be seen that the lack of epoxy-modified graphene oxide has a poor density of the carbonized layer, the oxygen and heat source barrier effect is limited, and the lack of synergy between the substances makes it impossible to form a complete flame retardant network, and the flame retardant effect is significantly affected; from the results of Comparative Example 2 and Example 2, it can be seen that the carbonized layer formed by ordinary graphene oxide at high temperature is not as dense as that of epoxy-modified graphene oxide, and the oxygen and heat source barrier effect is affected to a certain extent; from the results of Comparative Example 3 and Example 2, it can be seen that the unmodified nano-montmorillonite has poor dispersibility, the lamellar structure is difficult to distribute evenly, and the flame retardant barrier effect is weakened, which leads to a more obvious molten drop phenomenon, an accelerated combustion speed, and a significant reduction in the flame retardant effect; from the results of Comparative Example 4 and Example 2, it can be seen that the lack of structural support of glass fiber makes the material easy to deform when burning, which leads to a more obvious dripping combustion phenomenon.
[0036] Thermal stability test: The ABS composite flame retardant material samples prepared in Example 2 and Comparative Examples 1 to 4 and the control group (ABS material) were heated at a rate of 120°C / h, and their decomposition temperatures were recorded. The results are as follows: Figure 3 shown.
[0037] Depend on Figure 3 As can be seen from the results, the ABS composite flame retardant material prepared by the present invention has an extremely high decomposition temperature and excellent heat resistance; from the results of Comparative Example 1 and Example 2, it can be seen that the barrier effect is significantly reduced due to the lack of a dense carbonized layer of epoxy-modified graphene oxide, the interface bonding force cannot be effectively improved, and the dispersibility is poor, which makes the matrix easier to decompose at high temperatures; from the results of Comparative Example 2 and Example 2, it can be seen that the interface bonding force and dispersibility of ordinary graphene oxide are significantly weaker than those of epoxy-modified graphene oxide, and the density of the carbonized layer is poor, resulting in limited barrier effect and heat resistance being affected to a certain extent; from the results of Comparative Example 3 and Example 2, it can be seen that unmodified nano-montmorillonite is prone to uneven dispersion, and the lamellar structure is difficult to form an effective thermal barrier, resulting in increased heat accumulation inside the material, which in turn leads to an accelerated decomposition process; from the results of Comparative Example 4 and Example 2, it can be seen that the structural stability of the material is significantly affected at high temperatures due to the lack of rigid support of glass fiber, and the ability to block heat conduction is significantly reduced.
[0038] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A high-strength, corrosion-resistant ABS composite flame-retardant material, characterized in that: The composition includes the following raw materials in parts by weight: 60 to 75 parts of acrylonitrile-butadiene-styrene, 10 to 15 parts of glass fiber, 0.5 to 1 part of γ-aminopropyltriethoxysilane, 8 to 12 parts of phosphorus nitrogen flame retardant, 1 to 3 parts of nano aluminum oxide, 0.5 to 1 part of potassium perfluorooctane sulfonate, 1 to 3 parts of epoxy-modified graphene oxide, and 5 to 8 parts of modified nano montmorillonite; The specific preparation steps of the modified nano-montmorillonite are as follows: (1): Add nano-montmorillonite to anhydrous ethanol and perform ultrasonic treatment to obtain a nano-montmorillonite suspension; slowly drop octadecyltrichlorosilane into the nano-montmorillonite suspension, increase the temperature, control the pH to be neutral, and stir to react; (2): After the reaction in step (1) is completed, the mixture is allowed to stand and cool to room temperature, deionized water and ethanol are added for washing alternately, centrifuged, washed repeatedly, and vacuum dried at 60° C. to constant weight to obtain modified nano-montmorillonite.
2. The high-strength, corrosion-resistant ABS composite flame-retardant material according to claim 1, characterized in that: In step (1), the ratio of the amount of the nano-montmorillonite to the anhydrous ethanol is 1 g: 20-25 mL; the ratio of the amount of the octadecyltrichlorosilane to the nano-montmorillonite is 2-2.5 mL: 1 g.
3. The high-strength, corrosion-resistant ABS composite flame-retardant material according to claim 2, characterized in that: The specific preparation steps of the epoxy-modified graphene oxide are as follows: Ⅰ: adding graphene oxide to anhydrous ethanol and subjecting to ultrasonic treatment to obtain a graphene oxide dispersion; slowly adding 3-glycidyloxypropyltrimethoxysilane to the graphene oxide dispersion, increasing the temperature, and stirring the reaction; II: After the solution reaction in step I is completed, the solution is cooled to room temperature, washed with deionized water, centrifuged, washed repeatedly, and vacuum dried to constant weight to obtain epoxy-modified graphene oxide.
4. The high-strength, corrosion-resistant ABS composite flame-retardant material according to claim 3, characterized in that: In step I, the ratio of the amount of graphene oxide to deionized water is 0.1-0.2 g:50 mL; the ratio of the amount of graphene oxide to 3-glycidyloxypropyltrimethoxysilane is 0.5 g:0.8-1 mL.
5. The high-strength, corrosion-resistant ABS composite flame-retardant material according to claim 4, characterized in that: The phosphorus-nitrogen flame retardant is any one of tricresyl phosphate, trimethyl phosphate, triethyl phosphate and ammonium polyphosphate.
6. A method for preparing the high-strength, corrosion-resistant ABS composite flame-retardant material according to any one of claims 1 to 5, characterized in that: The specific preparation steps are as follows: S1: adding γ-aminopropyltriethoxysilane to anhydrous ethanol, stirring and mixing to obtain a coupling agent solution; immersing the glass fiber in the coupling agent solution, standing, and drying to constant weight to obtain a pretreated glass fiber; S2: adding epoxy-modified graphene oxide, modified nano-montmorillonite, phosphorus-nitrogen flame retardant, nano-alumina and potassium perfluorooctane sulfonate into a mixer in sequence, stirring and mixing to obtain a premix; S3: Add acrylonitrile-butadiene-styrene into an extruder, preheat and initially melt, then gradually add the premix prepared in step S2 and the pretreated glass fiber prepared in step S1, set the extrusion speed to 60-120 rpm, the melting temperature to 200-240° C., the extrusion speed to 1-3 m / min, and quickly cool the extruded material through a cooling water tank to obtain an ABS composite flame retardant material.
Citation Information
Patent Citations
Graphene / glass fiber reinforced ABS composite and preparation method thereof
CN105820496A
PPS (polyphenylene sulfide) resin composite material for corrosion-resistant end surface sealing strips and preparation method thereof
CN107523057A
High-performance fiber-reinforced thermoplastic halogen-free flame-retardant composite material and preparation method thereof
CN111154185A
Flame-retardant modified ABS composite material and preparation method thereof
CN113667264A
Cited By
Non-asbestos sealing plate and preparation method thereof
CN120682603A
Synergistic reinforced PC / ABS high-flame-retardant material and preparation method thereof
CN121362447A